PP.39.16: RENAL BIOPSY FINDINGS IN METHAMPHETAMINE USERS. (June 2015) - Jones, E.; Rayner, B.
Abstract : Objective: Methamphetamine abuse has risen dramatically in South Africa. The chronic effects of methamphetamine use on the kidneys and blood pressure have not been documented. This study reviewed the renal biopsies of patients referred for evaluation of kidney disease, who had been abusing methamphetamines. Design and method: All patients that underwent a renal biopsy who had been using methamphetamines between 2005 and 2013 were reviewed. Patient demographics, biophysical parameters, blood pressure, renal function, renal ultrasound and biopsy findings, complications of chronic kidney disease and co-morbidities were recorded. Results: Renal biopsies were performed in twenty-four patients. Twelve (50%) of the biopsies showed hypertensive changes and six had evidence of malignant hypertension. Fourteen (58%) had mesangiocapillary glomerulonephritis type 1 with deposition of IgM and C3. There was evidence of end stage renal disease in six (25%) biopsies. Conclusions: Methamphetamine use is associated with severe hypertension, mesangiocapillary glomerulonephritis and chronic kidney disease.